Pengembangan Media Pembelajaran Diorama Berbasis Digital Materi Jenis-Jenis Pekerjaan pada Siswa Kelas III Sekolah Dasar - Ulil Maknunah; Siti Umayaroh; Puri Selfi Cholifah (Universitas Negeri Malang, 2023)
Abstract: The purpose of this research is to develop diorama learning media about types of work for grade III elementary school students that are valid, practical, and interesting. This type of research is research and development, namely developing diorama learning media. This study uses the ADDIE research model step. The subjects in this study were grade 3 elementary school students, grade 3 teachers, media experts and material experts. The data collection techniques of this research are observation, questionnaire, interviews and documentation. The results of this research are diorama learning media with a level of validity of 97.08 percent and a level of practicality and attractiveness of 97.6 percent. Abstrak: Penelitian ini bertujuan guna kembangkan media belajar diorama tentang jenis-jenis pekerjaan guna siswa kelas III Sekolah Dasar yang valid, praktis, serta menarik. Jenis penelitian ini yaitu penelitian dan pengembangannya, yaitu mengembangkan media belajar diorama. Penelitian ini menggunakan langkah model penelitian ADDIE. Subjek pada penelitian ini yakni siswa kelas 3 sekolah dasar, guru kelas 3, ahli media serta ahli materi. Teknik pengumpulan data penelitian ini yaitu observasi, angket, wawancara serta dokumentasi. Hasil dari penelitian ini adalah media pembelajaran diorama dengan tingkat kevalidan 97,08 persen dan tingkat kepraktisan dan kemenarikan 97,6 persen.